Study on nano-CaCO3/NR composite prepared by emulsion co-precipitation method - Jiang Wang; Tongjian Zhao; Xin Fu (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.483-487.)
Calcium oxide, carbon dioxide and natural rubber latex were selected as main raw material, Na5P3O10 as crystal controlling agent, C12H25NaO3S modified agent and EDTA dispersant. Firstly the latex of nanometer calcium carbonate was prepared, then nanometer CaCO3 NR composites was prepared through the mixing and co-precipitation of nanometer calcium carbonate and natural rubber latex. The effects of Ca(OH)2 concentration, carbonization temperature, crystal controlling agents and dispersants on the properties of nanometer CaCO3/NR composites were investigated using static analytical method. The structure and properties of composites were studied using modern measurement methods such as SEM, TEM, DSC and mechanical measurements.
Keywords: Composite latex co-precipitation method; Nano-calcium carbonate; Natural rubber latex